2005
DOI: 10.1007/s11136-004-4231-z
|View full text |Cite
|
Sign up to set email alerts
|

International development of the Parents’ Index of Quality of Life in Atopic Dermatitis (PIQoL-AD)

Abstract: The PIQoL-AD is a valuable instrument for inclusion in clinical trials and routine clinical practice. It provides distinct and complementary information to that of existing dermatology-specific measures and has been shown to be responsive to changes in QoL in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 25 publications
1
79
0
Order By: Relevance
“…In common with other studies, 15,16 his study found that parents can feel that others are making negative judgements of their parenting if eczema affects their child's appearance. In addition, a few of the interviewees also felt judged by their healthcare provider and were upset and angry about this:…”
Section: Perceptions Of Doctorssupporting
confidence: 68%
See 1 more Smart Citation
“…In common with other studies, 15,16 his study found that parents can feel that others are making negative judgements of their parenting if eczema affects their child's appearance. In addition, a few of the interviewees also felt judged by their healthcare provider and were upset and angry about this:…”
Section: Perceptions Of Doctorssupporting
confidence: 68%
“…[15][16][17][18] The present study shows that these issues are also pertinent to the milder case mix seen in primary care, where the vast majority of cases are managed. Qualitative studies in other healthcare settings have found accounts of carers feeling that doctors do not take eczema seriously and that they offer insufficient information.…”
Section: Comparison With Existing Literaturementioning
confidence: 75%
“…Published scales for this purpose include the Children's Dermatology Life Quality Index, the Dermatitis Family Impact Scale, the Infants' Dermatitis Quality of Life Index, and the Parents' Index of Quality of Life for Atopic Dermatitis. [9][10][11][12] The CADIS (Childhood Atopic Dermatitis Impact Scale) is a QOL scale specifically for children with AD younger than 6 years and their parents ( Table 1). Based on existing knowledge about pediatric AD and QOL, the CADIS was developed from directed focus sessions with expert clinicians and parents of young children with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The Patient’s Overall Self-Assessment score included pruritus, sleep disturbances and general disease control of the patients. Quality of life was measured at screening, after 6 weeks of treatment and at the end of the study using the Children’s Dermatological Life Quality Index [9] and the Parents’ Index of Quality of Life-Atopic Dermatitis [10]. The patients/the patient’s caregivers reported the days of topical steroid use (i.e.…”
Section: Methodsmentioning
confidence: 99%